The Emergence of Social Work Practice Research in the Peoples' Republic of China: A Literature Review. (January 2017) - Sim, Timothy; Lau, Victor C. Y.
Objective: In China where social work is a fledgling profession, practice research is still a novelty. This article aims to provide an overview of the development of social work practice research in mainland China. Methods: This review analyzes the content of 206 Chinese journal articles published in the Peoples' Republic of China since 1915 using the China National Knowledge Infrastructure database, with a focus on the question "who published what?" Results: The first social work practice research was published in 1999 and it has been increasing in recent years in China. They are predominantly conducted by academics and the collaboration between academics and practitioners is rare and can be further promoted. Conclusions: Practice research could be stepped up to build a distinctive professional knowledge base for social work in China considering its unique geographical, cultural, socioeconomic, and political contexts.